Fracture precursor phenomena in marble specimens under uniaxial compression by means of Acoustic Emission data (Fracture and Structural Integrity, 2019)
Marble specimens are subjected to a specially designed stepwise loading protocol, in an attempt to detect fracture precursor phenomena taking advantage of Acoustic Emission (AE) data. The analysis is carried out in terms of the number of acoustic hits recorded and the time evolution of the improved b-value (Ib-value), the cumulative energy of the acoustic signals and the F-function. During the stage of increasing load, intense acoustic activity is detected as the corresponding stress reaches the transitional phase from the linear to the nonlinear mechanical response of the material. When the stress is stabilized at levels exceeding 95% of the material’s compressive strength, the acoustic activity is drastically reduced. During the first seconds of the stress stabilization stage the reduction follows an exponential law. Special attention is paid to the phases, where the occurrence of AE hits shows a strong increase. During these phases acoustic signals of low frequency and high RA are recorded, indicating that the micro-cracking process is of shear rather than of opening mode.
Keywords: Acoustic Emission; Marble; Compression; Ib-value; F-function; Micro-cracking classification